Three Essays on the Diffusion of Climate-smart Technology in Agriculture - Islam, Zeenatul (Curtin University, 2023)
This research evaluates the causal relations between climate-smart technology use and farmers’- financial understanding, pro-environmental behavior, and cooperation. It develops choice experiments for financial and environmental behaviors and novel measurements of cooperation. This research shows that climate-smart adopters have a high cognitive financial understanding, their pro-environmental behavior is action-oriented, and the economic efficiency of their farming improves with cooperation level. This research outlines significant policy implications for the diffusion of climate-smart agricultural technology.